2016
DOI: 10.1063/1.4964678
|View full text |Cite
|
Sign up to set email alerts
|

Molecular model for chirality phenomena

Abstract: Chirality is a hallmark feature for molecular recognition in biology and chemical physics. We present a three-dimensional continuum model for studying chirality phenomena in condensed phases using molecular simulations. Our model system is based upon a simple four-site molecule and incorporates non-trivial kinetic behavior, including the ability to switch chirality or racemize, as well as thermodynamics arising from an energetic preference for specific chiral interactions. In particular, we introduce a chiral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 59 publications
1
41
0
Order By: Relevance
“…These fluids form conglomerates which are capable of strong chirality amplification eventually leading to homogeneous chirality. Especially the observation of spontaneous chiral segregation in isotropic liquids provided a strong boost for the conformational chirality hypothesis, which is also supported by recent simulation work [114][115][116]. However, chirality synchronisation in the fluid state requires cooperativity, i.e.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…These fluids form conglomerates which are capable of strong chirality amplification eventually leading to homogeneous chirality. Especially the observation of spontaneous chiral segregation in isotropic liquids provided a strong boost for the conformational chirality hypothesis, which is also supported by recent simulation work [114][115][116]. However, chirality synchronisation in the fluid state requires cooperativity, i.e.…”
Section: Discussionsupporting
confidence: 58%
“…In contrast, it is usually argued that in the liquid state the energetic difference between the conformers is too small to give rise to any significant bias of molecular conformations and that the entropy of mixing disfavours enantiomeric segregation [36,85,105]. However, there is simulation work suggesting that spontaneous synchronisation of the helix sense of helical conformers ('ferrochirality') is possible in polymers [114], as well as in liquids [115,116], provided that the molecules are transiently chiral (see for example compound 4 in Figure 9(a)). Chirality synchronisation was previously suggested as origin of chirality in some nematic phases of bent-core molecules [84] though it turned out later that in this case director rotation by surface pinning of the nematic director appears to be more important (see Section 9) [117,118].…”
Section: Chirality Synchronisation In Mirror-symmetry Broken Isotropimentioning
confidence: 99%
“…A similar case is the symmetric phase separation of stereoisomers. A recent simulation study [94] One of the arguments in favor of the discrete approach is the direct computation of the equilibrium number of molecules involved in alternative states in several simulated water-like models. The fractions of molecules involved in the high-density structure and in the low-density structure at various temperatures and pressures have been computed for the ST2 [95], TIP4P/2005 [96] and mW [66,97] models.…”
Section: B Is Landau Theory Sufficient To Unify Different Polyamorphmentioning
confidence: 99%
“…[9][10][11] Despite much research activity, no definitive answers to these questions have been found. [12][13][14][15][16][17][18][19][20][21] In principle, thermodynamics dictates that the crystal with the lowest free energy prevails in equilibrium. Studies of chiral molecules a) Electronic mail: michael.gruenwald@utah.edu have shown, however, that thermodynamics alone cannot explain the bias towards racemic crystals observed in experiments.…”
Section: Introductionmentioning
confidence: 99%